Prevalence and molecular characterisation of Cryptosporidium from dairy cattle in five farms in Kuantan - Afzan Mat Yusof,; Muhammad Lokman Md Isa, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Cryptosporidium spp. are ubiquitous enteric protozoan parasites that cause diarrhoeal disease known as cryptosporidiosis. This research was conducted to find the prevalence of Cryptosporidium from dairy cattle in Kuantan, Pahang, Malaysia and to identify the genotype of Cryptosporidium by using 18S rRNA gene. Besides, this study aims to investigate the association between Cryptosporidium infection and the age of dairy cattle. A total of 375 stool specimens of dairy cattle were collected and concentrated with formal-ether concentration technique. The Cryptosporidium oocysts were detected with modified Ziehl Neelsen staining. Cryptosporidium species was identified by nested PCR amplification of 18S rRNA gene. Based on microscopic examination, 16.3% (61/375) dairy cattle were positive for Cryptosporidium infection. This research has shown that the highest prevalence of Cryptosporidium was recorded in calves with the percentage of 17.4% (12/69), followed by adult cattle and yearling with the percentage of 16.1% (29/180) and 15.9% (20/126), respectively. The findings demonstrated that there was no significant difference (p > 0.05) in Cryptosporidium infection rates by age. Molecular characterisation revealed that the species of Cryptosporidium found in dairy cattle was Cryptosporidium ryanae. The present study suggested that proper hygiene practices must be practiced by farmers in order to control the Cryptosporidium infection.